Development of FSK receiver for coherent optical fiber communication system - Mukkamala Kameshwar Rao. (2008)
The primary objective in this project is to develop a long wavelength fiber-optic receiver using the state of the art coherent detection technology, to maximise the repeater span length and data handling capacity.